Peningkatan Kemampuan Guru Dalam Manajemen Pengelolaan Kelas Di Masa Pandemi Covid-19 - Eliningsih Eliningsih (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2021)
The purpose of implementing this PTKp activity is to improve the ability of teachers in classroom management during the Covid 19 pandemic through clinical supervision of supervisors. The research subjects were 9 teachers. Data collection techniques through observation techniques, and documentation techniques. Descriptive qualitative data analysis by comparing the results from before the action and after the action. The results of data analysis show that there is an initial condition that only reaches a mean score of 57.34 with LESS criteria, increases to 78.97 with ENOUGH criteria, and in the last cycle it becomes 89.88 with GOOD criteria, and individually per teacher in the initial condition there is not yet. teachers who were declared complete, increased to 5 teachers or 55.56% and in the last cycle to 9 teachers or 100%. From the explanation above, it can be concluded that the implementation of clinical supervision has been proven to improve teacher performance in classroom management at SDN 15 Perawang Semester 2 of the 2020/2021 academic year.